Outcome of Staphylococcus aureus Bacteremia According to Compliance with Recommendations of Infectious Diseases Specialists: Experience with 244 Patients - Fowler, Vance G.; Sanders, Linda L.; Sexton, Daniel J.; Kong, Likuo; Marr, Kieren A.; Gopal, Ajay K.; Gottlieb, Geoffrey; McClelland, R. Scott; Corey, G. Ralph (Clinical infectious diseases, 1998)
To determine whether recommendations of infectious diseases specialists affect outcome for patients, we evaluated 244 hospitalized patients with Staphylococcus aureus bacteremia. We offered our management recommendations to each patient's physicians and then assessed the clinical outcome for both patients for whom our consultative advice was followed and those for whom our advice was not heeded. All patients were followed up for 12 weeks after their first positive blood culture. Our management advice was followed for 112 patients (45.9%) and partially or completely ignored for 132 patients (54.1%). Patients for whom our recommendations were followed were more likely to be cured of their S. aureus infection and less likely to relapse (P < .01), despite having significantly more metastatic infections (P < .01) at the outset of therapy, than were those for whom our recommendations were not followed. Failure to follow recommendations to remove an infected intravascular device was the most important risk for treatment failure. After controlling for other factors, logistic regression analysis revealed that patients whose intravascular device was not removed were 6.5 times more likely to relapse or die of their infection than were those whose device was removed. Our findings suggest that patient-specific management advice by infectious diseases consultants can improve the clinical outcome for patients with S. aureus bacteremia.